2019
DOI: 10.1016/j.arr.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Age-related diseases as vicious cycles

Abstract: Age-related diseases (ARDs) are the leading cause of death worldwide, and contribute to 90% of mortality in developed countries. Interestingly, the mortality rates of individual ARDs increase exponentially with age. Processes described by the exponential growth function typically involve a branching chain reaction or, more generally, a positive feedback loop. Here I propose that each ARD is mediated by one or several positive feedback loops (vicious cycles). I then identify critical vicious cycles in five majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 336 publications
1
36
0
3
Order By: Relevance
“…The human population is rapidly growing older [1,2], with a concomitant increase in agerelated diseases [2,3] and societal challenges. Much of the recent increase in human life span can be attributed to improved sanitation and medical advances; however, there is also a genetic component.…”
Section: Introductionmentioning
confidence: 99%
“…The human population is rapidly growing older [1,2], with a concomitant increase in agerelated diseases [2,3] and societal challenges. Much of the recent increase in human life span can be attributed to improved sanitation and medical advances; however, there is also a genetic component.…”
Section: Introductionmentioning
confidence: 99%
“…These differences suggest that may be cell-specific changes in autophagy during senescence. Nonetheless, it appears that in the liver, autophagy likely decreases with aging and may be involved in many age-related diseases such as NAFLD and Type 2 DM [1,3,11,12,36]. In this connection, we found that both senescent AML12 cells and livers from aged mice showed late autophagy block associated with increased intracellular fat content (Figure 5a-g).…”
Section: Senescent Cells Are Metabolically Hyperactive and Display A mentioning
confidence: 76%
“…Moreover, the mRNA expression of senescence marker genes, P53, P21 and P16 were increased in the senescent AML12 cells compared to control AML12 cells (Figure 1d). Similarly, the expression of these genes also was increased in livers from old mice (100-108 week age) compared to those from young mice (12)(13)(14)(15)(16)(17)(18)(19)(20) week age) (Figure 1e). Furthermore, multiple H2O2 treatments increased senescence since there was increased activated -Gal (SA -Gal)-positive cells (Figure 2a,b) and H2A.X-positive cells containing condensed chromatin in larger nuclei (Figure 2c,d).…”
Section: Senescence Induction and Validation In Aml12 Cellsmentioning
confidence: 82%
See 2 more Smart Citations